2013
DOI: 10.1016/j.jsv.2012.11.002
|View full text |Cite|
|
Sign up to set email alerts
|

Acoustic radiation force on a rigid cylinder in a focused Gaussian beam

Abstract: ABSTRACT-The acoustic radiation force resulting from a 2D focused Gaussian beam incident on cylindrical objects in an inviscid fluid is investigated analytically. The incident and the reflected sound fields are expressed in terms of cylindrical wave functions and a weighting parameter, describing the beam shape and its location relative to the particle.Our main interest here is to study the possibility of using Gaussian beams for axial and lateral handling of rigid cylindrical particles by exerting attractive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(19 citation statements)
references
References 54 publications
0
19
0
Order By: Relevance
“…not a force of attraction). In some situations, theoretical predictions have demonstrated the existence of a negative (pulling) force on a rigid cylinder in a focused Gaussian beam [42] (and spheres as well [43,44]), however, the mathematical expression for the incident Gaussian beam provided therein differs from Eq. (2).…”
Section: Numerical Results and Discussionmentioning
confidence: 99%
“…not a force of attraction). In some situations, theoretical predictions have demonstrated the existence of a negative (pulling) force on a rigid cylinder in a focused Gaussian beam [42] (and spheres as well [43,44]), however, the mathematical expression for the incident Gaussian beam provided therein differs from Eq. (2).…”
Section: Numerical Results and Discussionmentioning
confidence: 99%
“…It has been demonstrated that SBAT could trap the objects with a size either larger or smaller than an acoustic wavelength. 152,153 Hwang et al proposed a non-contact single-beam acoustic trapping method for the quantification of the mechanical properties of a suspended cell without any materials attached to the cell ( Fig. 16(b)).…”
Section: E Acoustic Trapsmentioning
confidence: 99%
“…10,11 On the other hand, the present analysis is based on the partial-wave series expansion (PWSE) method (known also as normal-mode decomposition in Fourier series) in cylindrical coordinates, and the evaluation of the beam-shape coefficients (BSCs) stemming from Graf's additional theorem for the cylindrical wave functions, without the need of numerical integration procedures, used previously in the method of the angular spectrum decomposition into plane waves, or in the computation of the acoustic radiation force on a rigid (sound impenetrable) cylinder. 12 It is also worth mentioning that the formalisms for the electromagnetic scattering of optical beams by (dielectric or perfectly conducting) cylindrical objects have used the angular spectrum and PWSE methods with numerical integration in several studies. [13][14][15][16][17][18] Nonetheless, the extension to predict and numerically compute the resonance scattering as well as the resulting acoustic radiation force using an exact method such as Graf's additional theorem, remains to be accomplished, which is developed here in this investigation.…”
Section: Introductionmentioning
confidence: 99%